Cyanobacteria-Derived Proline Increases Stress Tolerance in Arabidopsis thaliana Root Hairs by Suppressing Programmed Cell Death - Chua, Alysha; Sherwood, Orla L.; Fitzhenry, Laurence; Ng, Carl K.-Y.; McCabe, Paul F.; Daly, Cara T. (Frontiers in Plant Science, 2020)
Nitrogen-fixing heterocystous cyanobacteria are used as biofertiliser inoculants to stimulate plant growth. In addition, there have been suggestions that they can also alleviate plant stress through secretion of exometabolites to the rhizosphere. However, few studies have focused on elucidating the identity of the bioactive exometabolites involved due to the wide array of compounds that are exuded. Here, we used the root hair assay (RHA) as a rapid screening tool for programmed cell death (PCD) to characterise the bioactivity of the cyanobacteria Nostoc muscorum conditioned medium (CM) on Arabidopsis thaliana stress tolerance. We found that heat-stressed A. thaliana root hairs pre-treated with N. muscorum CM fractions exhibited significantly lower PCD levels compared to untreated seedlings. N. muscorum CM increased stress tolerance by suppressing PCD but not necrosis, indicating that the bioactive compound was specifically affecting the PCD pathway and not modulating a general stress response. Based on documented N. muscorum exometabolites, we identified proline, a stress-responsive amino acid as a compound of interest and the presence of proline in N. muscorum CM was confirmed using the ninhydrin assay and HPLC. To determine whether proline may function as the PCD-suppressing exometabolite, we conducted exogenous proline supplementation experiments and showed a similar effect on root hairs compared to N. muscorum CM, with slightly lower but similar PCD suppression levels and negligible changes in necrosis. To confirm proline as a bioactive compound in N. muscorum CM, we used three mutant A. thaliana lines with proline transporter mutations (lht1, aap1 and atprot1-1::atprot2-3::atprot3-2). Compared to wild-type seedlings, PCD-suppression in lht1and aap1 mutants were significantly reduced when supplied with low proline (1- 5 μM) levels, while all three mutant lines had higher PCD levels than wild-type seedlings treated with N. muscorum CM. Our results show that plant uptake of cyanobacteria-derived proline alters their PCD sensitivity threshold and primes the stress-acclimation response. This offers evidence of a novel biofertiliser mechanism which enhances plant stress tolerance independent of the existing mechanisms documented in the literature.